The Role Of Influencer Marketing and Brand Image In Forming Skincare Product Purchase Decisions: A Literature Review Study - Ana Nur Aeini; Edwin Zusrony; Putri Pratiwi (Denasya Smart Publisher, 2025)
This research is motivated by the increasing use of social media as a source of consumer information in selecting skincare products. Increasingly fierce competition among skincare brands means that companies cannot rely solely on product quality but also need to build credible digital marketing communications and a strong brand image. This study aims to examine the role of influencer marketing and brand image in shaping skincare product purchasing decisions based on previous research. The method used is a literature review study with a descriptive qualitative approach. The research data comes from eleven national scientific articles relevant to the topics of influencer marketing, brand image, purchase intention, and skincare or cosmetic product purchasing decisions. The articles were analyzed through the stages of identification, selection, content evaluation, grouping of findings, and narrative synthesis. The results of the study indicate that influencer marketing plays a role in attracting attention, building trust, and strengthening consumer purchasing interest through credibility, image congruence, and influencer closeness to the audience. Meanwhile, brand image serves as the basis for consumer confidence in the quality, safety, and reputation of the brand. This study also found that brand trust, online customer reviews, brand awareness, and electronic word of mouth are supporting variables that strengthen purchasing decisions. Thus, influencer marketing and brand image do not work separately, but complement each other in the process of forming skincare product purchasing decisions.